Competitive importance-performance analysis of an Australian wildlife park - Taplin, Ross (Pergamon, 2012)
Importance-Performance Analysis (IPA) and the related analysis of performance minus importance gaps have proved valuable and popular techniques for the management of tourism destinations as well as products and services more generally. Their simplicity makes them easily interpretable to management. Unfortunately their application is hindered by measurement bias and doubt over the appropriate placement of crosshairs to determine whether performance and importance is high or low. This paper introduces Competitive Importance-Performance Analysis (CIPA) to resolve these issues by applying the scientific principle of a control. CIPA uses benchmarking against competitors to determine cross-hair placement, reduce measurement bias and determine market position. A survey of an Australian wildlife park is used to illustrate how CIPA provides additional insights for management while results from IPA or gap analysis are potentially misleading. CIPA is applicable not only to tourism but also to other areas of management or marketing of a product or service.